The Rise of Concussions in the Adolescent Population. Issue 8 (16th August 2016) - Zhang, Alan L.; Sing, David C.; Rugg, Caitlin M.; Feeley, Brian T.; Senter, Carlin
Background: Concussion injuries have been highlighted to the American public through media and research. While recent studies have shown increased traumatic brain injuries (TBIs) diagnosed in emergency departments across the United States, no studies have evaluated trends in concussion diagnoses across the general US population in various age groups. Purpose: To evaluate the current incidence and trends in concussions diagnosed across varying age groups and health care settings in a large cross-sectional population. Study Design: Descriptive epidemiological study. Methods: Administrative health records of 8, 828, 248 members of a large private-payer insurance group in the United States were queried. Patients diagnosed with concussion from years 2007 through 2014 were stratified by year of diagnosis, age group, sex, classification of concussion, and health care setting of diagnosis (eg, emergency department vs physician's office). Chi-square testing was used for statistical analysis. Results: From a cohort of 8, 828, 248 patients, 43, 884 patients were diagnosed with a concussion. Of these patients, 55% were male and over 32% were in the adolescent age group (10-19 years old). The highest incidence of concussion was seen in patients aged 15 to 19 years (16.5/1000 patients), followed by those aged 10 to 14 years (10.5/1000 patients), 20 to 24 years (5.2/1000 patients), and 5 to 9 years (3.5/1000 patients). Overall, there was a 60% increase in concussion incidence from 2007 to 2014. The largest increases were in the 10- to 14-year (143%) and 15- to 19-year (87%) age groups. Based on International Classification of Disease–9th Revision classification, 29% of concussions were associated with some form of loss of consciousness. Finally, 56% of concussions were diagnosed in the emergency department and 29% in a physician's office, with the remainder in urgent care clinics or inpatient settings. Conclusion: The incidence of concussion diagnosed in the general US population is increasing, driven largely by a substantial rise in the adolescent age group. The youth population should be prioritized for ongoing work in concussion education, diagnosis, treatment, and prevention. Clinical Relevance: The rise of concussions in the adolescent age group across the general population is concerning, and clinical efforts to prevent these injuries are needed.